Dezertir . The Deserter - Pudovkin, Vsevolod (Merazhpom, 1934)
Duration: 01:41:00 "Deserter" follows the trek of a German worker who decides he can't keep working after a strike is called at his shipyard, to feed his family and for the continued glory of his homeland (Germany). Torn between hunger and solidarity for his fellow workers, he finally is sent to Russian to learn some lessons in socialism and comes back - not a deserter, but a hero. He's the seed of a new Socialist unity among the workers. The two most interesting aspects of this film is that it has a German striker as the lead protagonist, probably allowing Pudovkin to show his hero having doubts about the "cause" more easily without getting in trouble with the authorities; and also the use of sound. It's very primitive, with sound cutting in only when needed for dialog or sound effects for emphasis. Nevertheless, "Deserter" is powerful agitprop cinema from one of the Russian masters. Its political force is driven home by following a worker truly torn by unfair circumstances to the point of abandoning his fellow workers and family. It humanizes the struggle many Russian political filmmakers and montagists tried to capture in their important work in the 20s and 30s.